When one’s sense of agency goes wrong: absent modulation of time perception by voluntary actions and reduction of perceived length of intervals in passivity symptoms in schizophrenia - Graham-Schmidt, Kyran T.; Martin-Iverson, Matthew T.; Holmes, Nicholas P.; Waters, Flavie A.V. (Elsevier, 2016)
Passivity symptoms in schizophrenia are characterised by an absence of agency for actions, thoughts and other somatic experiences. Time perception and intentional binding have both been linked to agency and schizophrenia but have not been examined in passivity symptoms. Time perception and intentional binding were assessed in people with schizophrenia (n = 15 with, n = 24 without passivity symptoms) and 43 healthy controls using an interval estimation procedure (200, 400 and 600 ms intervals) with active, passive and ob- served movements. People with passivity symptoms did not display action-modulation of time perception, while those without passivity symptoms estimated intervals to be the same after active and observed move- ments. Additionally, both clinical samples reported intervals to be shorter with increasing interval length. We propose that impaired predictive processes may produce an overreliance on external cues and, together with shorter perceived intervals, lead to the subjective loss of agency